PENGEMBANGAN USAHA TERNAK SAPI POTONG BERORIENTASI AGRIBISNIS DENGAN POLA KEMITRAAN - Suryana Suryana (Jurnal Penelitian dan Pengembangan Pertanian, 2009)
Development of beef cattle agribusiness through partnership patternBeef cattle are the largest contributor of the ruminants to the national meat production, therefore cattle farming is potential to be developed. In Indonesia, cattle are raised traditionally by farmers as a family saving and as draught animal in land preparation. Beef cattle farming is commonly as a small-scale farming and consists of breeding, fattening, and integrated farming system with food crops or estate crops. Development of beef cattle agribusiness through partnership pattern could be an alternative approach in increasing farmers' incomes and national meat production. Partnership is a cooperation between two or more partners in beef cattle farming in preproduction, production processes, and marketing based on equally and profitable principles. The development of beef catlle farming through partnership pattern is expected to meet the national demand for meat that continuously increases. On the other hand, the high demand for beef cattle meat gives an opportunity to develop beef cattle farming in the country through partnership to increase production and productivity. This paper reviewed the development of beef cattle farming through partnership pattern. To achieve the high farming efficiency, it is needed to manage the system integratedly from upstream to downstream by applying the agribusiness principles and partnership pattern to obtain the high and sustainable profit.